2′-Hydroxy flavanone derivatives as an inhibitors of pro-inflammatory mediators: Experimental and molecular docking studies. Issue 9 (1st May 2015) - Patel, Neeraj K.; Bairwa, Khemraj; Gangwal, Rahul; Jaiswal, Gaurav; Jachak, Sanjay M.; Sangamwar, Abhay T.; Bhutani, Kamlesh K.
Graphical abstract The 2D interaction diagram of 13 at the active site of TNF-α.